2020
DOI: 10.1039/c9cc08296d
|View full text |Cite
|
Sign up to set email alerts
|

Nitro reduction-based fluorescent probes for carbon monoxide require reactivity involving a ruthenium carbonyl moiety

Abstract: Nitro reduction-based fluorescent CO probes only sense ruthenium-based CO donors, CORM-2 and CORM-3, not CO in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…The observed earlier CORM-2-mediated upregulation of Hmox1 mRNA in gastric mucosa exposed to ethanol or aspirin could be due to the presence of Ruthenium in the structure of CORM-2, which in fact, did not interfere with the potential gastroprotective activity of this CO donor 35 , 78 . It needs to be noted that recent studies have found that ruthenium-based CO-RMs such as CORM-2 can participate in many reactions under physiological conditions 68 , 69 , 70 , 71 , 72 , 73 , 74 . Thus, it is reasonable to conclude that the interpretation of the protective gastroprotective effects of CORM-2 can be attributed to yet unrecognized factors and mechanisms besides the release of CO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed earlier CORM-2-mediated upregulation of Hmox1 mRNA in gastric mucosa exposed to ethanol or aspirin could be due to the presence of Ruthenium in the structure of CORM-2, which in fact, did not interfere with the potential gastroprotective activity of this CO donor 35 , 78 . It needs to be noted that recent studies have found that ruthenium-based CO-RMs such as CORM-2 can participate in many reactions under physiological conditions 68 , 69 , 70 , 71 , 72 , 73 , 74 . Thus, it is reasonable to conclude that the interpretation of the protective gastroprotective effects of CORM-2 can be attributed to yet unrecognized factors and mechanisms besides the release of CO.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, ruthenium-based CORM-2 and CO have been studied for their gastroprotective and ulcer healing effects 30 , 31 , 33 . However, recent studies of ruthenium-based CO-RMS have led some to ask for “a major reappraisal of the biological effects of CORM-2 and related CORMs” 68 because of ruthenium's ability to undergo chemical reactions with thiols 68 , 69 , 70 and other molecules or proteins 71 , 72 , 73 , 74 . Recently, organic CO prodrugs have been shown to be effective in treating systemic inflammation, experimental colitis, chemically induced liver injury, and ischemia reperfusion kidney injury 17 , 22 , 64 , 75 .…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Wang et al 73 found that the CO uorescence probes based on the nitro-reduction reaction were not responsive to CO from all sources. The ruthenium carbonyl moiety (ruthenium core for activating the reduction action) was essential to causing the signal response of nitro reductionbased uorescent probes.…”
Section: Nitro Reductionmentioning
confidence: 98%
“…[62] But, very recently Wang et al makes one striking report about the authenticity of the chemical transformation occurring, i. e. transformation of the nitro group to amine due to CO gas. [63] They reported that after a prolonged purging of CO gas no observable spectroscopic changes were occurring and NIR-CO is not a general CO probe. They also interpreted that the ruthenium-based donors of CORMs are the administrator for the reduction of aryl-nitro group to aryl-amine and there is no role of CO.…”
Section: Fluorescent Probes For Non-targetable Co Detection In Livingmentioning
confidence: 99%
“…But, very recently Wang et al. makes one striking report about the authenticity of the chemical transformation occurring, i. e. transformation of the nitro group to amine due to CO gas . They reported that after a prolonged purging of CO gas no observable spectroscopic changes were occurring and NIR‐CO is not a general CO probe.…”
Section: Fluorescent Probes For Non‐targetable Co Detection In Livingmentioning
confidence: 99%